1987
DOI: 10.2527/jas1987.642420x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Plasma Flux and Oxidation of L-Leucine in Heifers at Two Levels of Intake1

Abstract: Four Hereford X Angus heifers (379 +/- 11 kg) with indwelling hepatic portal vein, iliac artery and mesenteric vein catheters were used in a switchback design to measure net portal absorption of leucine at two levels of energy intake, 130 and 260 kcal metabolizable energy.(kg.75.d)-1. Nine hourly measurements were made through two consecutive 4-h feeding periods on each heifer at each intake level. In separate experiments, N balance was determined and 6-h continuous infusions of L-[1-14C]-leucine were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
9
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
9
9
0
Order By: Relevance
“…For all AA, dietary restriction resulted in a numerical decrease in ILR irrespective of the type of sample (whole blood or plasma) analysed. Similar effects of feed intake on Leu ILR have been reported in beef cattle (Hammond et al 1987;Lobley et al 1987;Lapierre et al 1996Lapierre et al , 1999, sheep (Liu et al 1995) and dairy goats (Riis, 1988). The only exception to this finding was Glu, for which the ILR in restricted animals was numerically higher.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For all AA, dietary restriction resulted in a numerical decrease in ILR irrespective of the type of sample (whole blood or plasma) analysed. Similar effects of feed intake on Leu ILR have been reported in beef cattle (Hammond et al 1987;Lobley et al 1987;Lapierre et al 1996Lapierre et al , 1999, sheep (Liu et al 1995) and dairy goats (Riis, 1988). The only exception to this finding was Glu, for which the ILR in restricted animals was numerically higher.…”
Section: Discussionsupporting
confidence: 74%
“…One way to measure the total body flux of an AA in animals is by quantifying the dilution of a tracer substance (Reeds, 1992;Lobley, 1993). Both radioactive (Hammond et al 1987;Lobley et al 1987;Crompton & Lomax, 1993) and stable isotopes (Bequette et al 1994;Liu et al 1995;Lapierre et al 1996Lapierre et al , 1999 have been used to label AA for this purpose. A technique using the infusion of a mixture of 13 C-universally labelled AA of algal origin has allowed the simultaneous estimation of the whole-body fluxes of an array of AA.…”
mentioning
confidence: 99%
“…03 of plasma LeuTR, the isotope infused would not influence plasma LeuTR. Plasma LeuTR was comparable with those reported in growing cows (Hammond et al 1987;Dawson et al 1998;Lapierre et al 1999). Lobley et al (1987) studied the effect of progressive reduction in food intake on WBPS with the [1-14 C]Leu method in finishing beef steers and found that food intake influenced overall protein metabolism.…”
Section: Discussionsupporting
confidence: 70%
“…Based on the lack of a dietary difference in the rate of whole-body protein synthesis, it might therefore be concluded that in the present experiment duodenal flows of amino acids were similar for the two diets. This is unlikely though, as the greater leucine entry and oxidation rates, and greater plasma leucine concentrations of animals fed dried grass (Table 5), are indicative of greater leucine absorption on this diet, as these parameters have been shown to be a function of intake (Meguid et al 1986;Hammond et al 1987;Lapierre et al 2002;Savary-Auzeloux et al 2003). This is supported by the effect of MEI, and thus protein intake as the relative composition of the diets remained unchanged, on these parameters associated with whole-body protein metabolism.…”
Section: Protein Metabolismmentioning
confidence: 90%